Frances Wright’s America: A 19th-Century Utopia - Fruzińska, Justyna (Text Matters: A Journal of Literature, Theory and Culture, 2020)
Frances Wright, a British social reformer and feminist, published an account of her American travels: Views of Society and Manners in America in 1821. Wright founded an experimental community in Nashoba, Tennessee, whose aim was to buy black slaves, educate them, and then liberate them. Even though the enterprise turned out to be a failure, the author continued to fight for the cause of black emancipation. My paper examines Wright’s portrayal of America in Views, which, compared to most other early 19th-century British travel accounts, is surprisingly enthusiastic. Wright idealizes the young republic, seeing it as a perfect embodiment of her ideals. I argue that Wright’s vision of the young republic is utopian, and it prevents her from seeing any flaws in the American system. This is especially pronounced in the case of the central problem posed by British travelogues of the era, slavery, which troubles her not so much on moral grounds, but as a blemish on the character of the country of freedom and equality.